A State-Of-The-Art Review on Sars-Cov-2 Virus Removal Using Different Wastewater Treatment Strategies - Sandoval, A; Sandoval, A (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
In addition to the numerous health effects caused by the COVID-19 pandemic, the scientific community has considered other emerging effects such as water-related impacts worthy of deep investigation. In this regard, the transmission cycles of the SARS-CoV-2 virus from fecal, vomiting, and sputum routes to sewage have led health authorities to diagnose, prevent, and use novel wastewater treatment technologies. Once they enter the gastrointestinal canal of a healthy person, viral particles can infect via the nominal amount of Angiotensin-Converting Enzyme 2 (ACE2) present in alimentary canal epithelial cell surfaces and further infect lung, heart, kidney, and other organs. The current review highlights the detection, status, and fate of SARS-CoV-2 from sewage treatment facilities to water bodies. Besides, it addresses the potential wastewater treatment processes to cope with various viruses, especially SARS-CoV-2. Many processes can manage contaminated wastewater and solid wastes over the long term, including membrane technologies, disinfectants, UV-light and advanced oxidation methods like photocatalysis, ozonation, hydrogen peroxide, nanomaterials, and algae. Future work must focus on implementing the selected actions for the treatment of the wastewater released from the COVID-19 hospitals and self-quarantine centers to better regulate future waves of SARS-CoV-2. © 2022 by the authors.